(untitled) (Africa Development, 1984)
CONTENTS International Debt Renegotiation: Ghana's Experiences Eboe HUTCHFUL ......................... 5 The Present Crisis of the Tanzanian Economy: Notes on the Economics and Politics of Devaluation Ajit SINGH ........................ 28 Approche Marxiste et Production de Connaissances sur l'Agriculture Nacer BOURENANE ...................... 44 Underdevelopment and the Politics of Sierra Leone's Trade Relations Yusuf BANGURA ......................... 71 Etudes des Marchés et des Perspectives d'Echanges Céréaliers des Pays de l'Afrique de l'Ouest: Sénégal, Mali, Haute Volta, Côte d'Ivoire, Ghana, Nigéria, Cameroun Mahmoud ALLAYA .......................... 92 BOOK REVIEWS 1./ Lee, Eddy (ed.) Export-led Industrialization and Development (ILO) - Asian Employment Programme, Bangkok (1981) 2./ Frobel F., Heinriches J. and Kreye O. - The New International Division of Labour (Cambridge University Press, 1980) ........ 143 FOCUS ON RESEARCH AND TRAINING INSTITUTES Laboratoire d'Analyse et de Recherches Economiques et Sociales(L.A.R.E.S.)-Université Marien Ngouabi .................149 BOOKS RECEIVED .....................154